New Solutions for the Modelling and Design of a Hand Exoskeleton System - Mazzotti, Claudio <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
Recently, a prototype of a hand exoskeleton for post-stroke rehabilitation purpose was proposed by the Group of Robotics, Automation and Articular Biomechanics (GRAB) at the Department of Industrial Engineering, University of Bologna. The prototype comprises five planar mechanisms (one per finger) globally actuated by two DC motors. A total of fifteen human-machine connections are needed to fasten the device to the patient hand. The moving link of the thumb mechanism is actuated by a spatial RSSR mechanism whose frame link geometry must be ad hoc regulated every time the device is fitted on the patient hand. With the future goal to build a new version of the hand exoskeleton, in this dissertation three problems arising from this prototype were tackled. The first problem regards the need to lower the number of human-machine connections needed to fasten the exoskeleton to the patient hand. A new finger mechanism that permits to lower the total number of human-machine connections from fifteen to only six was proposed. The second problem regards the synthesis of the RSSR mechanism. A novel synthesis procedure was proposed in order to guarantee the optimal motion and force transmission to the thumb mechanism once the hand exoskeleton is fitted to a new patient, i.e. for different frame link geometries of the RSSR mechanism. The third problem regards the need to approximate the finger phalange motion as a rotation about a revolute axis. In this perspective, two different joint axes identification techniques were proposed. The techniques are based on the Burmester theory (a theory generally used for the synthesis of mechanisms), here used in an original way to identify an axis of rotation. A comparison of this two technique with a more standard technique based on the finite helical axis is reported.